Determination of insolation conditions and selection of the optimal orientation of residential buildings - Yurin, Yurin; Zyhun, Alina; Galinska, Tatiana; Avramenko, Yurii (Academic journal Industrial Machine Building Civil Engineering, 2021)
The project is devoted to the determination of insolation conditions and the choice of optimal orientation of residential buildings, considering the latitude of the terrain of Poltava. Presently, there is a change from construction according to standard designs to individual design and the process of consolidation of residential construction in cities continues by new construction in the historic built-up areas. Compacting and increasing the number of floors inevitably worsens insolation in the living rooms of existing houses due to the additional shading of their windows, which leads to a decrease in the duration of insolation. The factor of rational planning of the territory and the optimal orientation of the house on the cardinal points, the correct choice of floors and configuration in the plan get special significance.
Keywords: duration of insolation; optimal orientation of the residential building; insolation ruler